1996
DOI: 10.1111/j.1476-5381.1996.tb15418.x
|View full text |Cite
|
Sign up to set email alerts
|

Ability of angiotensin II to modulate striatal dopamine release via the AT1 receptor in vitro and in vivo

Abstract: 1 The ability of angiotensin II to modulate dopamine release from rat striatal slices in vitro and in the intact rat striatum in vivo was assessed by the microdialysis technique.2 In slices of rat striatum, angiotensin II (0.1-1.0 gM) induced a concentration-related increase in endogenous dopamine release which was maximal (approximately 250% above basal levels) within the first 2-4 min of agonist application and subsequently declined to near

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
54
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(60 citation statements)
references
References 50 publications
3
54
0
Order By: Relevance
“…Furthermore antagonist of AT1Rs has been shown to be neuroprotective [116]. Interaction between AII and DA was suggested by early microdialysis studies, which showed that acute AII perfusion induces DA release and the effect was blocked by AT1Rs antagonists [106,117]. The mechanism responsible for the AII induced DA release has not been completely clarified, although it's been thought that involvement of D2 auto-receptors could be participating [106].…”
Section: Renin-angiotensin Systemmentioning
confidence: 99%
“…Furthermore antagonist of AT1Rs has been shown to be neuroprotective [116]. Interaction between AII and DA was suggested by early microdialysis studies, which showed that acute AII perfusion induces DA release and the effect was blocked by AT1Rs antagonists [106,117]. The mechanism responsible for the AII induced DA release has not been completely clarified, although it's been thought that involvement of D2 auto-receptors could be participating [106].…”
Section: Renin-angiotensin Systemmentioning
confidence: 99%
“…The brain possesses a local angiotensin system (Gendron et al, 2003;McKinley et al, 2003;Pan, 2004;Rodriguez-Pallares et al, 2004), and the results of previous studies have suggested that AII and its receptors play an important role in modulating striatal dopamine (DA) levels. Both AII and AII receptors as well as angiotensinogen and angiotensin-converting enzyme (ACE) have been observed in the striatum (Quinlan and Phillips, 1981;Brownfield et al, 1982;Chai et al, 1987;Allen et al, 1992Allen et al, , 1998, and AII stimulates the release of newly synthesized DA via angiotensin type 1 receptors (AT 1 ) located in the striatal DA terminals (Mendelsohn et al, 1993;Brown et al, 1996;Ge and Barnes 1996). However, it has recently been shown that in several cell types, including neurons, reactive oxygen species (ROS) play a crucial role in the signaling of AII via AT 1 receptors.…”
mentioning
confidence: 98%
“…14 For example, when angiotensin II was introduced by microdialysis into the striatum, the level of dopamine increased to three times baseline. 15 On the other hand, stimulation of the angiotensin type 2 (AT 2 ) receptor, which has been expected to play a protective role in RAS.…”
Section: Introductionmentioning
confidence: 99%